Utilization of Jengkol (Pithecellobium jiringa) Peel Biochar and Chicken Manure as Organic Fertilizer on Red Chili Plants (Capsicum annum L) in Acidic Dry Land - Rosmiah Rosmiah; R. Iin Siti Aminah; Dessy Tri Astuti; Neni Marlina; Dewi Meidalima; Beta Pratama (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2023)
Chili (Capsinum annum) is a horticultural plant that is useful as a spice in the kitchen, besides containing vitamins that are good for health. This study aimedÂ as an effort to make jengkol skin agricultural waste useful by adding chicken manure organic fertilizer at different doses with the potential to increase growth and yield of chili plants on acidic dry land. The field experiment was conducted on the land of the Food Crops Agriculture Office, Gandus District, Palembang from March to May 2022. Randomized factorial group experimental design with 2 factors, namely the first factor: the dose of Jengkol Peel Biochar fertilizer (B) consisting of: B1 = 5 tons/ha, B2 =15 tons/ha, B3=25 tons/ha. The second factor: the dose of chicken manure (K) consists of: K0 = 0 (without fertilizer chicken manure), K1 = 10 tons/ha, K2 = 20 tons/ha, K3 = 30 tons/ha. Growth and yield were observed by measuring plant height (cm), stem diameter (cm), number of productive branches (branches), chili weight per plant (g), chili weight per plot (g). The best trial was obtained in the combination treatment dose of 15 tons/ha of jengkol peel biochar fertilizer and 30 tons/ha of chicken manure, which was the best treatment for the growth and production of chilies, with a yield per plot of 343.5 g/plant or equivalent to 10.99 tons/ha.